2022
DOI: 10.1039/d2nj01530g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystal size on the acidity of nanometric Y zeolite: number of sites, strength, acid nature, and dehydration of 2-propanol

Abstract: Little is known about how the variation in crystallite size of zeolites affects acidity. There is currently a tendency to decrease the size of materials because of the resulting improvements...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…34,35 The band close to 1490 cm −1 corresponded to the combination of Brønsted acid and Lewis acid. 36 It was conspicuous from the PY-IR spectra that the H-MBeta zeolite has the largest Brønsted acid sites among these zeolites. The calculation results demonstrated that the H-MBeta zeolite had a higher number of Brønsted acid sites (175 μmol g −1 ) than Na-MBeta (116 μmol g −1 ), H-MBeta-0.3 (127 μmol g −1 ), and H-MBeta-1.0 (79 μmol g −1 ), (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The band close to 1490 cm −1 corresponded to the combination of Brønsted acid and Lewis acid. 36 It was conspicuous from the PY-IR spectra that the H-MBeta zeolite has the largest Brønsted acid sites among these zeolites. The calculation results demonstrated that the H-MBeta zeolite had a higher number of Brønsted acid sites (175 μmol g −1 ) than Na-MBeta (116 μmol g −1 ), H-MBeta-0.3 (127 μmol g −1 ), and H-MBeta-1.0 (79 μmol g −1 ), (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…11 These treatments have not only been found to improve the physicochemical and catalytic properties of zeolites but have also produced microporous zeolite-type materials containing a secondary system of larger pores (hierarchical zeolites). 12–14 Although most studies assessing post-synthesis treatments have been applied to micrometric zeolites, only a few have been focused on their influence on the structure and acidity of submicroscale zeolites 15,16 with potential application in catalysis. 17…”
Section: Introductionmentioning
confidence: 99%
“…Propene is a vital industrial raw material and intermediate, 1–5 which can be used to manufacture acrylic acid, acrylonitrile, acrolein, and other important chemicals. Additionally, it is an important component in synthetic materials such as plastics, fibers, and rubber, with a wide range of applications and has considerable economic value.…”
Section: Introductionmentioning
confidence: 99%